The Dynamics of Foreign Direct Investment and Privatization: An Empirical Analysis - Boubakri, Narjess; Cosset, Jean-Claude; Debab, Nassima; Valéry, Pascale (Management international / Gestiòn Internacional / International Management, 2009)
AbstractThis article examines the link between foreign direct investment (FDI) and privatization of state-owned enterprises. We hypothesize that privatization has an effect on FDI as the process of fostering private sector participation is often accompanied by liberalization measures, and by allocating the shares of newly privatized firms to foreign investors. Similarly, we expect FDI to foster privatization efforts as capital inflows, technology and managerial skills that accompany FDI make the environment more prone to competition, and provide governments with a good environment to privatize inefficient firms. Our results provide support for our conjectures.